2007
DOI: 10.1186/1742-9994-4-21
|View full text |Cite
|
Sign up to set email alerts
|

Do cleaning organisms reduce the stress response of client reef fish?

Abstract: Background: Marine cleaning interactions in which cleaner fish or shrimps remove parasites from visiting 'client' reef fish are a textbook example of mutualism. However, there is yet no conclusive evidence that cleaning organisms significantly improve the health of their clients. We tested the stress response of wild caught individuals of two client species, Chromis dimidiata and Pseudanthias squamipinnis, that had either access to a cleaner wrasse Labroides dimidiatus, or to cleaner shrimps Stenopus hispidus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 39 publications
1
42
1
Order By: Relevance
“…Our data together with those of Bshary et al (2007) suggest that parasite removal by cleaner wrasses might not change average basal levels of cortisol substantially although it might reduce the peak levels of the hormone during stressful events. High peak levels of cortisol indicate a deficiency in the availability of metabolic resources under stressful conditions and this may have lasting and costly consequences for homeostatic processes, immunity, and reproductive behaviors (McEwen and Wingfield, 2003;Schreck, 2010).…”
Section: Effect Of Cleaners On Indicators Of Stress Of Reef Fishsupporting
confidence: 55%
See 4 more Smart Citations
“…Our data together with those of Bshary et al (2007) suggest that parasite removal by cleaner wrasses might not change average basal levels of cortisol substantially although it might reduce the peak levels of the hormone during stressful events. High peak levels of cortisol indicate a deficiency in the availability of metabolic resources under stressful conditions and this may have lasting and costly consequences for homeostatic processes, immunity, and reproductive behaviors (McEwen and Wingfield, 2003;Schreck, 2010).…”
Section: Effect Of Cleaners On Indicators Of Stress Of Reef Fishsupporting
confidence: 55%
“…An important element of this response in fish is the activation of the hypothalamus-pituitary-interrenal axis, which results in an increase in circulating levels of cortisol. Bshary et al (2007) showed for two client species (in the same study site as we used) Pseudanthias squamipinnis and Chromis dimidiatus that cortisol levels in response to a stressor were higher when these clients were resident on reef patches without cleaner access than with cleaner access. Here we aimed to test whether a similar effect could be measured in the basal levels.…”
Section: Effect Of Cleaners On Indicators Of Stress Of Reef Fishmentioning
confidence: 86%
See 3 more Smart Citations